Odpowiedź :
Odpowiedź:
1.
xa = xb + z
xa - z = xb
b = (xa - z)/x
xa - xb = z
x(a - b) = z
x = z/(a - b)
2.
P = a²√3/4
4P = a²√3
a² = 4P/√3
a = √[(4P/√3) = 2√(P/√3) = 2√(P√3/3)
3.
2xy + x = xz
2xy + x - xz)= 0
x(2y + 1 - z) = 0
x = 0/(2y + 1 - z) = 0
4.
y = 2x(x + x)
y= 2x²+ 2xc
2xc = y - 2x²
c = (y - 2x²)/2x
5.
(a + b)/a = x
a + b = ax
a - ax = - b
a(1 - x) = - b
a = - b/(1 - x)
6.
ay/x = z/y
ay * y = xz
ay² = xz
x = ay²/z
y = √(xz/a)
z = ay²/x
Odpowiedź:
xa = xb + z
xb = xa - z /:x
b = (xa - z)/x
xa = xb +z
xa - xb = z
x(a - b) = z /:(a - b)
x = z/(a - b)
p = a²√4 a = ? /:√4
a² = p/√4 = p/2
a = √p/2
2xy + x = xz x = ?
2xy + x - xz = 0
x(2y + 1 - z) = 0 /:(2y + 1 - z)
x = 0
y = 2x(x + c) c = ? /:2x
x + c = y/2x
c = y/2x - x
(a + b)/a = x a = ?
1 + b/a = x
b/a = x - 1
a(x - 1) = b /:(x - 1)
a = b/(x - 1)
ay/x = z/y x = ? /*x
xz/y = ay /*y/z
x = ay²/z
ay/x = z/y y = ? /*y
ay²/x = z /*x/a
y² = xz/a
y = √(xz/a)
ay/x = z/y z = ? /*y
z = ay²/x
Szczegółowe wyjaśnienie: